Teachers’ Perceptions of the Seven Domains of Technological Pedagogical Content Knowledge - Singh, Renu (Academic Voices: A Multidisciplinary Journal, 2019)
This study investigated teachers’ perceptions of the seven domains of TPACK. Based on the design of case study, 20 university teachers from different disciplines were purposively selected to participate in the study. Semi-structured interview was used to collect the data. The thematic analysis of the findings revealed that almost all teachers had higher level of primary knowledge domainsrelated to content knowledge (CK), pedagogical knowledge (PK), and pedagogical content knowledge (PCK )in comparison to the domain knowledge with technological knowledge; technological knowledge (TK), technological content knowledge (TCK), technological pedagogical knowledge (TPK), and technological pedagogical content knowledge (TPACK). Thus, they are unable to practice the framework of TPACK for technology integrated interventions into their pedagogy. The study contributes for the better understanding of the teachers’ perceptions of TPACK that will be useful for teacher educators, researchers, practitioners, and curriculum designers.